Buhay Ko-Lehiyo, School Culture of College Students in a State University: Inputs Toward a Culturally Responsive Teaching - Ebro, Eric D. S.; Caparoso, Rhodeleeyah D.; Burnasal, Norilyn O.; Mina, Heidi T.; Orteza, Geraldine R. (Future Science / FSH-PH Publications, 2025)
This study aimed to better understand the school culture of college students at a state university and develop culturally responsive teaching strategies. Teachers can create instructional strategies that connect with their cultural backgrounds, including their values, beliefs, behaviors, norms, languages, and experiences, to improve students' learning. The study employed a sequential explanatory mixed-method design, collecting and analyzing quantitative and qualitative data. Experts, including an area specialist and a language specialist, validated the instrument used for data collection. Eighty-three respondents were selected for the study. Quantitative results revealed that respondents positively embraced and perceived the school culture as shown in the composite mean of 3.45 (SD = 0.34), verbally interpreted as